(untitled) (Revista "Boletín el Conuco", 2021)
This article is the product of the research work that was developed in the framework of the in- terinstitutional doctorate in education, aims to contribute to the search of the relation of the technological artifacts with the science, the tech- nology, the Society, the environment and its con- tribution to the company. The findings seek from the question: Is it possi- ble to do archaeology to technological artifacts to reveal the relations that it has with science, te- chnology, society, the Environment and the com- pany, to generate a strategy for the learning of the Technology and the literacy of human talent? The working hypothesis on this question is affir- mative and it is proposed that the artifacts being the result of a technological and social process they can reveal such relationships of concepts. From this assumption, the discourse plays a deci- sive role in the qualification of the subjects. The methodology used, will allow to establish that the contributions of the theory of the discour- se Help to organize an archaeological method to observe the technological artifacts or more specifically what the hermeneutics can make as a method.